PENGARUH KOMUNIKASI ORGANISASI TERHADAP MOTIVASI KERJA GURU DAN KARYAWAN SMK NEGERI 1 PURWODADI - Nursari,, Rahma (Solidaritas, 2018)
Abstract: Does Organizational Communication has a significant influence on Work Motivation for Teachers and Non-Teaching Staff at SMK Negeri 1 Purwodadi? This research was conducted at SMK Negeri 1 Purwodadi with the subject of Teachers and Non-Teaching Staff at SMK Negeri 1 Purwodadi with the number of 40 people. The research method used in the research is quantitative research, type eksplanatif. . The result of the research is known that organizational communication yields regression coefficient 9.75 and significant level of 9.75> 3.25. For the coefficient of determination generated r2 coefficient value of 0.450. So it can be interpreted that as much as 45% can be explained by organizational communication to work motivation of teachers and employees. The remaining 55% are explained by causes outside the organizational communication variable. The conclusion of organizational communication has a positive and significant effect on teacher work motivation and employees.Â Keywords : Organizational Communication, teacher, staff, motivation to work